Communicative action seeking golden years! - Thereza Maria Magalhães Moreira (Rev Rene)
Over the year of 2015 much has been said and celebrated about the 15 years of Rene. Profesor Lorita Pagliuca, the journal’s founder and my first counselor in research, in the editorial number one, brilliantly rescued, based on the doctor Saramago’s work, that “utopia is the spice of life” and warned that social responsibility preserves the affection and inclusive do over the magazine’s evolution(1).